Evaluation of Reuse of Spent Mushroom Substrate for New Pleurotus ostreatus Crop Cycle - Vieira, Wagner Gonçalves [UNESP]; da Silva Alves, Lucas [UNESP]; de Moura, Jadson Belém; de Paula, Adriano Taffarel Camargo [UNESP]; da Silva Freitas, Marcos Antônio [UNESP]; Orti, Manuel Álvarez; Alegría, Francisco José Gea; Zied, Diego Cunha [UNESP] (MDPI, 2025)
Although considered relatively sustainable, mushroom production generates significant waste at the end of cultivation. This study investigated the reuse of Spent Mushroom Substrate (SMS) to formulate new substrates for Pleurotus ostreatus cultivation. Substrates with high (higher bran content) and low (lower bran content) nitrogen levels were prepared and supplemented with 5%, 10%, or 20% SMS across three successive cycles P. ostreatus crops. Cultivation performance was evaluated based on biological efficiency, number of mushrooms, fresh weight, and number of clusters. Substrates were chemically characterized for total nitrogen, carbon, C/N ratio, electrical conductivity, and pH. The inclusion of SMS, along with reduced bran content, did not improve P. ostreatus yield and led to lower productivity compared to control substrates. No consistent correlations were observed between chemical variables and yield, although high-N substrates generally performed better. SMS reuse, under these conditions, is not viable, but results encourage further research.